Carbene-catalyzed access to thiochromene derivatives: control of reaction pathways via slow release of thiols from disulfides - Wu, Qifei (2023)
Substrates containing disulfide bonds, which are more stable and less smelling, could be used as thiophenol precursors in organic synthesis. Herein, an N-heterocyclic carbene (NHC)-catalyzed reaction between α-bromoenals and 2,2'-dithiodibenzaldehydes was developed. Through the sustained release strategy, the side reaction can be effectively inhibited, and the chiral thiochromene derivatives can be obtained with good yields and high optical purities. Application studies showed encouraging results when the desired products were explored for antimicrobial utilities in pesticide development.